Gott, Mensch und Geschichte : Studien zum Verständnis des Menschen und seiner Geschichte in der klassischen, biblischen und nachbiblischen Literatur - Kaiser, Otto, 1924-2017 (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2010)
This volume of essays contains studies on the understanding of man and his history from Herodotus to Augustine, with focus on late biblical wisdom, early Jewish poetry and historiography as well as on the problem of mythological language, morality in antiquity and time.